Nanopartículas de Co suportadas em SiO2: síntese, caracterização e propriedades catalíticas para a reforma a vapor do etanol - Ribeiro, Renata Uema (Universidade Federal de São Carlos, 2007)
Colloidal Co Nanoparticles (Co-NPs) were used to prepare supported Co catalysts. The Co- NPs were obtained by thermal decomposition of the precursor Co2(CO)8 in the presence of oleic acid and trioctylphosphine oxide (TOPO), in an inert atmosphere (Ar). The Co- NPs/SiO2 were obtained by impregnation of a colloidal suspension of nanoparticles on the support no-porous SiO2. The effect of the solvent (ethanol and methanol) used in the step of precipitation of the particles, and by tuning the oleic acid/precursor ratio in the catalytic properties for the steam reforming of ethanol were investigated. The catalysts were characterized by Specific Superficial Area (SBET) and Fourier Transform Infrared Spectroscopy of the CO adsorbed (FTIR-CO). By tuning the oleic acid/precursor ratio it was possible to obtain particles sizes in the 2 and 17nm range. The results of FTIR-CO showed that the samples present the band of CO lineally adsorbed in the same position independent of the synthesis conditions, suggesting similar electronic density of the sites of Co. The results of adsorption of H2 and CO suggest that the fraction of acessible sites of Co so much to H2, as to CO, depends on the particles sizes and the residual oleic acid . Then with the increase of the particles sizes, there is a maximum of accessible sites of Co. For the same particle size, it is obtained an increase of the number of accessible sites of Co, using methanol as solvent for precipitation, suggesting smaller recovering. The catalysts prepared with Co-NPs present profiles of similar catalytic activity for the steam reforming of ethanol. Starting from reaction data a mechanism was proposed: in low temperatures, the molecule of ethanol adsorbs in the catalyst surface and it suffers dehydrogenation producing acetaldehyde. The increase of the temperature favors the formation of species CH4 and CO, suggesting the crack of the C-C bond of acetaldehyde for the formation of these products. The activity for the reforming reactions on the Co-NPs/SiO2 begins in approximately 350ºC, suggesting that the activation of the water occurs in this temperature. Therefore it is suggested the oxidation of adsorbed species CHx and CO for the formation of the products CO e CO2, respectively, occurred in temperatures above 350ºC. The catalytic activity depends on the fraction of accessible sites of Co. The reactions results demonstrate that the catalysts prepared with methanol presented higher catalytic activity for the reforming reaction, possibly due to the presence of a larger number of accessible sites of Co.
Keywords: Catálise; Nanopartículas; Cobalto; Catalisadores; Reforma; ENGENHARIAS::ENGENHARIA QUIMICA